Direct Coaptation of the Phrenic Nerve With the Posterior Division of the Lower Trunk to Restore Finger and Elbow Extension Function in Patients With Total Brachial Plexus Injuries. Issue 2 (February 2016) - Wang, Shu-feng; Li, Peng-cheng; Xue, Yun-hao; Zou, Ji-yao; Li, Wen-jun; Li, Yucheng
Abstract : BACKGROUND: To overcome the mismatch in nerve sizes in phrenic nerve transfer to the radial nerve for elbow and finger extension reanimation for patients with total brachial plexus injuries (TBPI), a selective neurotization procedure was designed. OBJECTIVE: To investigate the long-term results of phrenic nerve transfer to the posterior division of the lower trunk with direct coaptation in restoring elbow and finger extension after TBPI. METHODS: Phrenic nerve was transferred to and directly coapted with the posterior division of the lower trunk in 27 patients with TBPI. Seven patients were <18 years old (adolescent group), and the remaining 20 patients ≥18 years (adult group). RESULTS: Postoperative mean follow-up period was 54 ± 9 months (range, 48-85 months). The motor function attained M3 or greater in 81.5% of patients for elbow extension and in 48% of patients for finger extension. The percentage of patients who regained M3 or greater muscle power of finger extension in the adolescent group and the adult group was 71.4%, and 40%, respectively. Meanwhile, 85.7% in the adolescent group and 80% in the adult group achieved M3 or greater muscle power of elbow extension. There were no significant differences between the 2 groups. The elbow extension and finger extension were synchronous contractions and did not become independent of respiratory effort. CONCLUSION: This procedure simultaneously and effectively restores the function of elbow and finger extension in patients after TBPI. However, the patients could not do elbow and finger extension separately. ABBREVIATIONS: CC7, contralateral C7 FEV1, forced expiratory volume in 1 second FVC, forced vital capacity LT, lower trunk MMV, maximum voluntary ventilation PDLT, posterior division of lower trunk TBPAI, total brachial plexus avulsion injury TBPI, total brachial plexus injury TLC, total lung capacity Abstract : Supplemental Digital Content is Available in the Text.